Predicting Factors of Mothers on Oral Health Services among Preschool Children in Thailand - อัศวกุล วรวรรณ (Journal of Health Science of Thailand, 2020)
The objective of this study was to investigate predicting factors of mothers on oral health services among preschool children. The studied samples consisted of 913 mothers of 3–5 years old children and their child. They were selected by using multi–stage random sampling method. Mothers were requested to respond to the study questionnaires (summated rating scales). The oral health status of children were examined by dentists using WHO form (dmft index). Data were analyzed by Pearson’s correlation coefficient and stepwise multiple regression analysis. The results showed that ll 3 aspects of the predictive factors could predict maternal behavior on oral health services for preschool children. For receiving dental health promotion services, the predictors could account for 48.9%, with the first predictor was the favorable action tendency receiving oral health services (Beta=0.50, p<0.05). For receiving oral health prevention services, the predictors could account for 35.0%, with the first predictor was the favorable action tendency receiving oral health services (Beta=0.33, p<0.05). For receiving dental treatment, the predictors could account for 40.2%, with the first predictor was the future orientation (Beta=0.33, p<0.05). Thus, dental personnel and related health facilities should support mothers’ preparedness and concern in taking their children to receive oral health services while having no dental problem in order to have good oral health in the future.